ASSESSING MOTOR REHABILITATION OF POST-STROKE PATIENTS USING THE MOTOR ASSESSMENT SCALE - Tuyết, Trần Thị Kim; Nghĩa, Phan Trọng; Trường, Nguyễn Văn Nhật; An, Trần Viễn (Journal of Health and Aging, 2025)
To evaluate the motor function recovery in post-stroke patients using the motor assessment scale (MAS). A prospective, interventional, cross-sectional descriptive study without a control group, with assessments before and after treatment. The study was conducted on 92 post-stroke patients who received examination and treatment at the Rehabilitation Department, Emergency Cardiology Intervention Department, Neurology Department, and Traditional Medicine Department of Thong Nhat Hospital from May 2023 to May 2024. Motor function recovery was evaluated using the MAS scale, which includes 8 main activities: lying, sitting, standing, walking, and upper limb and hand movements. Motor function improved significantly after treatment, with an average increase of 5.58 ± 0.83 points (p<0.001). The position-shifting group showed greater improvement compared to the upper limb and hand movement group. The position-shifting score increased by 4.17 ± 0.5 points, while upper limb and hand activity scores increased by 0.86 ± 0.06 points. Activities that showed marked improvement included transitioning from supine to side-lying, from lying to sitting, achieving sitting balance, and standing up from a seated position. Upper limb and hand function requires more time to achieve full rehabilitation.